دور البيئة والملاءمة في الإقبال على مراكز التسوق "دراسة مسحية على مراكز التسوق في الساحل السوري" - برهوم أديب; المـشـحرة ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدُف هذا البحث إلى معرفة تأثير بعض العوامل الداخلية. كالبيئة والملاءمة، ودورها في زيادة إقبال المتسوقين على مراكز التسوق في الساحل السوري, وبالتالي معرفة مدى تأثر الإقبال على مراكز التسوق بهذين العاملين. تمَّ جمع المعلومات الأولية للبحث من خلال استبيان تم توزيعه على عيّنة ملاءمة من مرتادي مراكز التسوق في الساحل السوري. وتم تحليل هذه البيانات من خلال برنامج الـ SPSS الإحصائي. وبعد الدراسة والتحليل كان من أهم نتائج هذا البحث: 1- وجود ارتباط واضح فيما بين بيئة مركز التسوق المريحة والنظيفة وأيضاً الملاءمة الجيدة من جهة وزيادة الإقبال على مراكز التسوق في الساحل السوري من جهة أخرى. 2- أكد البحث على وجود قصور في الاهتمام بنواحي البيئة والملاءمة في المراكز الموجودة في منطقة الساحل السوري. 3- سجل البحث مجموعة من الملاحظات أهمها عدم توفر مطاعم كافية ومتنوعة في مراكز التسوق, وعدم اعتبار الكثير من أفراد العينة لهذه المراكز بوصفها مقصداً رئيساً للتسوق. This research aims to find out the impact of some internal factors such as the environment and appropriate and its role in increasing the turnout of shoppers on shopping centers in the Syrian Coast, thus find out the extent of influenced of demand for shopping centers by these two factors. Research primary information were collected through a questionnaire was distributed to an appropriate sample of shopping centers attendees, the data were analyzed by the SPSS statistical program. After the study and analyze the research reached to some of the important results: 1- There is a clear Correlation between the clean and comfortable shopping center environment and also good convenience on the one hand and increasing turnout for shopping centers in the Syrian coast on the other hand. 2- The research confirmed that there is a shortening of attention to aspects of the environment and appropriate in the shopping centers located in the Syrian Coast. 3- The research found some observations as well such as lack adequate and varied restaurants in shopping centers, and lot of shoppers they don’t consider the studied shopping centers as a major shopping destination.